Komunikasi Modem Serial Dengan Menggunakan Point To Point Protocol Pada Sistem Operasi Linux - Rostianigsih, Silvia (JIK: Jurnal Ilmu Komputer, 2004)
Linux Operating System which growing rapidly this day start to attract many people, especially academic and proffesionals in computer's world. Many things which make Linux more attractive is the open source's characteristic, which mean its application is freely available to everyone. In fact, we can get the source code easily, and the. stabilize as an operating system getting admission to many society. Linux also can maike a connection between modem, even internet. Linux also support the client-server system. Therefore, Local Area Network system can use only one modem as the connection for many computers to go through the internet. Point to point protocol is one of the protocols which used to do the connection to the internet or LAN, because of a lot of things its provided easily, especially the installation and the used of it.Kata Kunci :Ã‚Â  point to point protocol. unite, client-server.